Gender and American social science : the formative years - Silverberg, Helene, 1958- (Princeton, N.J. : Princeton University Press, 1998)
This collection of essays provides the first systematic and multidisciplinary analysis of the role of gender in the formation and dissemination of the American social sciences in the late nineteenth and early twentieth centuries. Other books have traced the history of academic social science without paying attention to gender, or have described women's social activism while ignoring its relation to the production of new social knowledge. In contrast, this volume draws long overdue attention to the ways in which changing gender relations shaped the development and organization of the new social knowledge.
And it challenges the privileged position that academic - and mostly male - social science has been granted in traditional histories by showing how women produced and popularized new forms of social knowledge in such places as settlement houses and the Russell Sage Foundation.
Introduction: toward a gendered social science history / Helene Silverberg -- pt. 1. Discourses of gender in the social sciences: The "sphere of women" in early-twentieth-century economics / Nancy Folbre. "Politics would undoubtedly unwoman her": gender, suffrage, and American political science / Mary G. Dietz and James Farr. "Wild West" anthropology and the disciplining of gender / Kamala Visweswaran -- pt. 2. Gender as constitutive of social science: Hull-House maps and papers: social science as women's work in the 1890s / Kathryn Kish Sklar. "A government of men": gender, the city, and the new science of politics / Helene Silverberg. The establishment of an applied social science: home economists, science, and reform at Cornell University, 1870-1930 / Nancy K. Berlage -- pt. 3. Social science as cultural critique: Gendered social knowledge: domestic discourse, Jane Addams, and the possibilities of social science / Dorothy Ross. Bringing social science back home: theory and practice in the life and work of Elsie Clews Parsons / Desley Deacon. The "self-applauding sincerity" of overreaching theory, biography as ethical practice, and the case of Mary van Kleeck / Guy Alchon.
Includes bibliographical references.
Print version record.
JSTOR
Keywords: Social sciences -- United States -- History; Women social scientists -- United States -- History; Women -- United States -- History; Sex role -- United States -- History; Femmes spécialistes des sciences sociales -- États-Unis -- Histoire; Femmes -- États-Unis -- Histoire; Rôle selon le sexe -- États-Unis -- Histoire; SOCIAL SCIENCE -- Women's Studies; Sex role; Social sciences; Women; Women social scientists; United States; Begriff; Frauenforschung; Geschichte; Geschlecht; Geschlechterverhältnis; Geschlechterforschung; Sozialwissenschaften; Sozialwissenschaftlerin; Wissenschaftsentwicklung; USA; Aufsatzsammlung; Sekseverschillen; Sociale wetenschappen; Social sciences -- United States -- History; Women social scientists -- United States; Women -- United States -- History; Sex role -- United States -- History; Aufsatzsammlung; History